CyberKnife radiation therapy as a platform for translational mouse studies. (2nd September 2021) - Kiljan, Martha; Weil, Sabrina; Vásquez-Torres, Andres; Hettich, Meike; Mayer, Marimel; Ibruli, Olta; Reinscheid, Matthias; Heßelmann, Isabelle; Cai, Jiali; Niu, Li-na; Sahbaz, Yagmur; Baues, Christian; et al.
Abstract: Purpose: Radiation therapy (RT) is a common nonsurgical treatment in the management of patients with cancer. While genetically engineered mouse models (GEMM) recapitulate human disease, conventional linear particle accelerator systems are not suited for state-of-the-art, imageguided targeted RT (IGRT) of these murine tumors. We employed the CyberKnife (CK; Accuray) platform for IGRT of GEMM-derived non-small cell lung cancer (NSCLC) lesions. Material and methods: GEMM-derived Kras LSL-G12D/+ /Trp53 fl/fl -driven NSCLC flank tumors were irradiated using the CK RT platform. We applied IGRT of 2, 4, 6, and 8 Gy using field sizes of 5–12.5 mm to average gross tumor volumes (GTV) of 0.9 cm3 using Xsight Spine Tracking (Accuray). Results: We found that 0 mm planning target volume (PTV) margin is sufficient for IGRT of murine tumors using the CK. We observed that higher RT doses (6–8 Gy) decreased absolute cell numbers of tumor infiltrating leukocytes (TIL) by approximately half compared to low doses (2–4 Gy) within 1 h, but even with low dose RT (2 Gy) TIL were found to be reduced after 8–24 h. Conclusion: We here demonstrate that the CK RT system allows for targeted IGRT of murine tumors with high precision and constitutes a novel promising platform for translational mouse RT studies.